Editorial: Practices, Representations and Meanings of Human Mobility in Archaeology - Gori, Maja; Revello Lami, Martina; Pintucci, Alessandro (Ex Novo: Journal of Archaeology, 2018)
Every society experiences movement. As a structural component of human behavior and human mind, movement necessarily influences our ways of thinking, our relationship with people, space, time, and traditions; it modifies how we organize as groups, our perception of things and the way in which we interact with them. For its role in shaping societies, mobility has been at the core of archaeology since its inception as a discipline. Throughout archaeology’s history, key topics focusing on the movement of people have included, among others: migration and diffusion; identity; invasion, conquest, and imperial imposition; colonialism; trade and the movement of goods, people, and animals; seafaring and its associated technologies; resource acquiring practices; nomadism. However, especially following the processual turn, scholars tended to minimize the impact of movement on human history placing instead major emphasis on theories about culture and its inherent mutability (e.g. Trigger 1989, Anthony 1990). As a result, despite decades of research into the nature of mobility by anthropologists, sociologists and geographers along with the most recent and sometimes controversial contributions of hard sciences – mainly strontium (Sr) and oxygen (O) isotope analysis, and aDNA analyses (on aDNA see Vander Linden 2016, Furholt 2018 and the controversial connection between cultural and biological identities in Lazaridis et al. 2017) – much archaeological debate seems still to revolve around two polarizing positions: those using movement as all-in-one explanatory device, and those that downgrade its role as active agent in triggering change.